PENGEMBANGAN STRATEGI PAROCS UNTUK MENGUBAH KONSEPSI ALTERNATIF SISWA PADA KONSEP KELEMBAMAN - Nuzulira Janeusse Fratiwi; Achmad Samsudin; Firmanul Catur Wibowo; Supriyatman Supriyatman; Bayram Costu (JURNAL TARBIYAH, 2022)
The aim of this study was to develop a Prediction, Alternative conceptions, Refutation, Observation, Comparison and Scientific explanation (PAROCS) strategy to change students’ alternative concepts on inertia concept. The research method used is the 4D model (Define, Design, Develop and Disseminate). Participants were 30 students (15 boys and 15 girls, their average age were 15-16) in class X of a public high school in Sukabumi, West Java. The instrument used is a four-tier diagnostic test. Data were analyzed based on a 4D model and conceptual category. At the disseminate stage, it shows an increase in scientific concepts and a decrease in alternative concepts after the application of the PAROCS strategy. From this, it can conclude that PAROCS strategy can be developed to change students’ alternative concepts into scientific concepts. Further studies could not only use the PAROCS strategy, but also develop this strategy for different physics concepts.